Cannabinoid receptor types 1 and 2 and peroxisome proliferator‐activated receptor‐α: distribution in the skin of clinically healthy cats and cats with hypersensitivity dermatitis. Issue 4 (19th June 2018) - Miragliotta, Vincenzo; Ricci, Pier Luca; Albanese, Francesco; Pirone, Andrea; Tognotti, Danika; Abramo, Francesca
Abstract : Background: Cannabinoid receptors and peroxisome proliferator‐activated receptor‐alpha (PPAR‐α) are gaining recognition as potential therapeutic targets for the treatment of skin disorders. Hypothesis/Objectives: The aim of this study was to investigate the distribution of cannabinoid type 1 and 2 receptors (CBR1 and CBR2) and PPAR‐α in feline skin and verify whether changes occur in the course of hypersensitivity dermatitis. Animals: Twelve privately owned cats. Skin samples were obtained from five healthy cats with no skin lesions and seven cats clinically diagnosed with hypersensitivity dermatitis. Methods and materials: Haematoxylin and eosin stained skin sections were investigated for histopathological changes. Indirect immunofluorescence for CBR1, CBR2 and PPAR‐α was performed on paraffin‐embedded sections, and antibody specificity tested by Western blot analysis. Results: Skin samples from cats with hypersensitivity dermatitis were all histopathologically diagnosed with eosinophilic dermatitis. CB receptors and PPAR‐α were distributed throughout the skin in both healthy and allergic cats. In normal feline skin, these receptors were mainly distributed in the epithelial compartment. Receptor expression increased in hypersensitivity compared to healthy skin, with the main distribution changes being suprabasal for CBR1, dermal for CBR2 and marked expression of PPAR‐α in hyperplastic epidermis and perivascular infiltrate. Conclusions and clinical importance: Increased expression of cannabinoid receptors in the skin of cats with hypersensitivity dermatitis suggests an endogenous protective strategy and may support the use of natural cannabinoid receptor or PPAR‐α agonists to treat feline hypersensitivity dermatitis. Abstract : Background – Cannabinoid receptors and peroxisome proliferator‐activated receptor‐alpha (PPAR‐α) are gaining recognition as potential therapeutic targets for the treatment of skin disorders.Hypothesis/Objectives – The aim of this study was to investigate the distribution of cannabinoid type 1 and 2 receptors and PPAR‐α in feline skin and verify whether changes occur in the course of hypersensitivity dermatitis.Conclusions and clinical importance – Increased expression of cannabinoid receptors in the skin of cats with hypersensitivity dermatitis suggests an endogenous protective strategy and may support the use of natural cannabinoid receptor or PPAR‐α agonists to treat feline hypersensitivity dermatitis.